Approach to the Verbal Morphology of Costa Rican Guaymí Spanish - Marín Esquivel, Rebeca (2021)
Key features of the verbal morphology of Spanish spoken by three indigenous speakers of the Costa Rican Guaymí/Ngäbe ethnic group are described and analyzed. Audio material was transcribed from interviews with two bilingual Guaymí-Spanish speakers and one Spanish monolingual son of bilingual Guaymí-Spanish parents. In this exploratory study, the irregular forms of the paradigms analyzed were found to show signs of regularizing the roots most closely resembling their infinitive, in addition to the creation of verbal neologisms.